The Factors Affecting Surplus Underwriting of Tabarru Funds in Sharia Life Insurance Companies - Tri Azmi Ramadhani; Tri Inda Fadhila Rahma; Muhammad Ikhsan Harahap (Indonesian Journal of Economics and Management, 2023)
The underwriting surplus is the difference in excess of the total contribution of participants that is included in the tabarru' fund plus assets and deducting claim payments and other costs. This article aims to analyze the factors that influence the acquisition of tabarru fund underwriting surplus in Islamic life insurance companies. The variables used in this study are contributions, claims, and investment returns as independent variables, then the underwriting surplus of tabarru funds as the dependent variable. The population used is sharia life insurance companies registered with the Financial Services Authority for the 2017-2021 period using the panel data regression method. The results of this study indicate that there is an influence on the contribution to the underwriting surplus of tabarru' funds because the greater the contribution obtained by the company, the underwriting surplus will increase, claims do not affect the underwriting surplus of tabarru' funds because if a claim occurs it will reduce the tabarru' funds, and investment returns does not affect the underwriting surplus of tabarru' funds because the company's investment management is still not optimal.